2004
DOI: 10.1590/s1519-566x2004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Development, longevity, gonotrophic cycle and oviposition of Aedes albopictus Skuse (Diptera: Culicidae) under cyclic temperatures

Abstract: The experiments were carried out with mosquitoes from Registro, São Paulo, Brazil, kept in insectary for two years. The development of the insect was followed from egg to adult emergence under 25/18ºC and 27/20ºC and adult stage under 27/20ºC, both associated with LD 12:12h. The eggs received two treatments: (A) maintenance of water volume; (B) periodical and complete change of water. Blood meal was offered daily and it was interrupted after haematophagy and restarted after first oviposition. The immature deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…The solid line represents the mean and the red shade represents the 95% confidence interval. (a) 1: [ 52 ], (b) 1: [ 71 ], 2: [ 72 ], 3: [ 58 ], 4: [ 46 ], 5: [ 73 ], 6: [ 74 ], 7: [ 75 ], 8: [ 76 ], 9: [ 77 ], 10: [ 78 ], 11: [ 79 ], 12: [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The solid line represents the mean and the red shade represents the 95% confidence interval. (a) 1: [ 52 ], (b) 1: [ 71 ], 2: [ 72 ], 3: [ 58 ], 4: [ 46 ], 5: [ 73 ], 6: [ 74 ], 7: [ 75 ], 8: [ 76 ], 9: [ 77 ], 10: [ 78 ], 11: [ 79 ], 12: [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…aegypti densities were positively correlated with rainfall only. According to Vezzani (2004) [31,32], ambient temperatures over 20.8 °C and rainfall higher than 150 mm are suitable for Ae. aegypti population increase.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in Ae. albopictus found that females tended to live longer than males (Löwenberg and Navarro‐Silva , Delatte et al ).…”
Section: Discussionmentioning
confidence: 99%